Hild Protection in Family Law Based on Parenting: A Study in The Community of Golewa District - Prisko Yanuarius Djawaria Pare; Yasinta Maria Fono (Lembaga Bale Literasi, 2026)
Children are individuals who have not yet reached adulthood and remain under the responsibility of their parents or guardians in physical, mental, and social aspects. The essence of this study emphasizes the most relevant model of legal protection that can be applied within families based on the provisions of Indonesian family law. One aspect that needs empirical examination is the model of legal protection in families based on parenting, or proper and appropriate parenting practices, within the community of Golewa District, Ngada Regency. The general objective of this study is to identify and analyze the implementation of child protection in parenting-based family law within the Golewa District community, as well as to assess its effectiveness in ensuring the fulfillment of children’s rights and to analyze the forms of parenting practices applied in families in relation to child protection. The method used in this study is empirical legal research (socio-legal), employing a juridical approach to examine legal norms related to child protection and a sociological approach to observe parenting practices in community life. The expected output of this study is a parenting-based child protection model in family law that is relevant to the local context of the Golewa District community, as well as a contribution to the development of family law, particularly from an empirical (socio-legal) perspective. This research also supports the strengthening program of the 7th Asta Cita of the Government of the Republic of Indonesia.